CHALLENGES OF UNIVERSITY TEACHING (Annual of the Faculty of Philosophy in Skopje, 2007)
The article focuses on the university teaching as a segment of university education with a great importance for the creation of professional competences and personal qualities of the citizens of the learning society. Emphasis is given to the elaboration of three key aspects of the university teaching: teaching-research relationship, aims and objectives of teaching and learning, and the issue of teaching methodology. Each of these topics is a subject of analysis and critical assessment of its historical and contemporary understanding and meaning.
Keywords: UNIVERSITY TEACHING; RESEARCH; AIMS AND OBJECTIVES; TEACHING METHODOLOGY